Slow cortical potential and theta/beta neurofeedback training in adults: effects on attentional processes and motor system excitability - Studer, Petra; Kratz, Oliver; Gevensleben, Holger; Rothenberger, Aribert; Moll, Gunther H.; Hautzinger, Martin; Heinrich, Hartmut (Frontiers in Human Neuroscience, 2014)
Neurofeedback (NF) is being successfully applied, among others, in children with ADHD and as a peak performance training in healthy subjects. However, the neuronal mechanisms mediating a successful NF training have not yet been sufficiently uncovered for both theta/beta (T/B), and slow cortical potential (SCP) training, two protocols established in NF in ADHD. In the present randomized controlled investigation in adults without a clinical diagnosis (n = 59), the specificity of the effects of these two NF protocols on attentional processes, and motor system excitability were to be examined, focusing on the underlying neuronal mechanisms. NF training consisted of 10 double sessions, and self-regulation skills were analyzed. Pre- and post-training assessments encompassed performance and event-related potential measures during an attention task, and motor system excitability assessed by transcranial magnetic stimulation. Some NF protocol specific effects have been obtained. However, due to the limited sample size medium effects didn’t reach the level of significance. Self-regulation abilities during negativity trials of the SCP training were associated with increased contingent negative variation amplitudes, indicating improved resource allocation during cognitive preparation. Theta/beta training was associated with increased response speed and decreased target-P3 amplitudes after successful theta/beta regulation suggested reduced attentional resources necessary for stimulus evaluation. Motor system excitability effects after theta/beta training paralleled the effects of methylphenidate. Overall, our results are limited by the non-sufficiently acquired self-regulation skills, but some specific effects between good and poor learners could be described. Future studies with larger sample sizes and sufficient acquisition of self-regulation skills are needed to further evaluate the protocol specific effects on attention and motor system excitability reported.